Soft polishing antifouling ceramic tile and preparation method thereof

By using hierarchical structure and antibacterial protein coupled antifouling coating in soft light ceramic tiles, the problem of poor antifouling performance is solved, and higher antifouling and antibacterial effects are achieved, improving the wear resistance and use effect of the ceramic tiles .

CN119118625APending Publication Date: 2024-12-13ZI BO SHI WANG TAO CI YOU XIAN GONG SI

Patent Information

Application Number
CN202411256862.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing soft light ceramic tiles have poor anti-fouling performance and cannot effectively resist stains, which affects their use effect.

Method used

The flexible and anti-fouling ceramic tile design adopts a hierarchical structure, including a blank layer, a base glaze layer, a pattern layer, a protective glaze layer and an anti-microbial protein coupled anti-fouling coating. Through the use of modified serpentine and anti-microbial protein conjugates, Improve the hardness and wear resistance of ceramic tiles, and enhance the antifouling performance by spraying antibacterial protein coupled antifouling coating.

Benefits of technology

It significantly improves the anti-fouling performance of ceramic tiles, can effectively resist water and oily stains, enhances the antibacterial properties and wear resistance of ceramic tiles, and improves the overall use effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118625A_ABST
    Figure CN119118625A_ABST
Patent Text Reader

Abstract

The invention discloses a soft polishing antifouling ceramic tile and a preparation method thereof, and belongs to the technical field of ceramic tiles. The soft polishing antifouling ceramic tile sequentially comprises a green body layer, a ground glaze layer, a pattern layer, a protective glaze layer and an antibacterial protein coupling antifouling coating from bottom to top, the coating is formed by combining N-succinimide-3-(2-pyridyl dithio) propionate with antibacterial protein to form a stable amido bond, polyethylene glycol methacrylate is added to introduce a polyethylene glycol chain, and the antibacterial protein coupling antifouling coating is formed by combining the N-succinimide-3-(2-pyridyl dithio) propionate with the antibacterial protein. And finally, an ethanol solution is added, so that the prepared coating can effectively resist various stains. The soft polishing antifouling ceramic tile disclosed by the invention has a good soft light effect and antibacterial and antifouling properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic tiles, and in particular relates to a soft-polished anti-fouling ceramic tile and a preparation method thereof. Background Art

[0002] With the continuous improvement of people's living environment and the improvement of aesthetic standards, the choice of home decoration materials is no longer limited to practicality and durability, but more attention is paid to its comprehensive impact on human health, psychological feelings and environmental coordination. As one of the important materials for indoor and outdoor decoration, the optimization of the gloss of ceramic plates has become the focus of industry attention. Consumers are increasingly inclined to products that can show taste, create a warm and comfortable atmosphere, and take into account environmental protection and health.

[0003] The gloss treatment of traditional ceramic tiles often relies on high-intensity polishing technology. Although this treatment method can give the tiles an extremely high mirror effect, it also brings about the problem of light pollution that cannot be ignored. Being in such an environment for a long time can easily cause eye fatigue and even affect vision health. At present, the use of soft polishing technology instead of traditional polishing technology can achieve fine control of the microstructure of the tile surface, thereby maintaining a certain gloss while greatly reducing the intensity of reflected light, creating a soft and comfortable visual experience. However, the existing production process of soft light ceramic tiles has the disadvantages of uneven polishing, destruction of the glaze crystal structure, and poor anti-fouling performance. Therefore, a soft-polished anti-fouling tile is developed to solve the technical problem of poor anti-fouling performance of soft light tiles in the prior art. Summary of the invention

[0004] The object of the present invention is to provide a soft-polished anti-fouling tile and a preparation method thereof, so as to solve the technical problem that the anti-fouling performance of the soft-polished tile in the prior art is poor.

[0005] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: the present invention provides a soft-polished anti-fouling ceramic tile, which comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer, a protective glaze layer and an antibacterial protein coupled anti-fouling coating; the body layer comprises the following raw materials in parts by weight: 42 to 46 parts of ceramic recycled materials, 20 to 45 parts of kaolin, 32 to 35 parts of dolomite, 26 to 28 parts of wollastonite, 25 to 32 parts of albite, 12 to 16 parts of potassium feldspar, 15 to 30 parts of high-alumina clay and 20 to 25 parts of modified serpentine; the base glaze layer comprises a base glaze layer, a pattern layer, a protective glaze layer and an antibacterial protein coupled anti-fouling coating; the base glaze layer comprises the following raw materials in parts by weight: 42 to 46 parts of ceramic recycled materials, 20 to 45 parts of kaolin, 32 to 35 parts of dolomite, 26 to 28 parts of wollastonite, 25 to 32 parts of albite, 12 to 16 parts of potassium feldspar, 15 to 30 parts of high-alumina clay and 20 to 25 parts of modified serpentine; The glaze layer comprises the following raw materials in parts by weight: 22-35 parts of albite, 12-26 parts of potassium feldspar, 12-25 parts of quartz sand, 3-6 parts of magnesium oxide and 2-8 parts of aluminum oxide; the protective glaze layer comprises the following raw materials in parts by weight: 35-43 parts of frit, 52-65 parts of suspended glue, 3-6 parts of polyethylene wax emulsion, 1-2 parts of penetrant, 6-8 parts of albite, 6-8 parts of potassium feldspar, 5-10 parts of quartz, 2-4 parts of calcined talc, 2-3 parts of barium carbonate, 4-5 parts of calcined zinc oxide and 3-8 parts of kaolin.

[0006] Furthermore, the ceramic recycled material comprises the following raw materials in parts by weight: 50-60wt% ceramic waste, 5-30wt% clay, 5-20wt% quartz sand, 5-10wt% feldspar and 5-10wt% additives; the additives are one or more of talc, dolomite, borax, boric acid, iron oxide and aluminum oxide.

[0007] Furthermore, when preparing the modified serpentine, the serpentine is crushed to 50-80 μm, heated to a temperature of 470-500° C. at a rate of 2-3° C. / min, kept warm for 50-70 min, and then heated to 1100-1200° C. at a rate of 1.2-2.0° C. / min, and then a sodium aluminate solution with a concentration of 80-95 mg / L and an equal weight to that of the serpentine is added, mixed evenly, kept warm for 40-60 min, and naturally cooled to room temperature to obtain the modified serpentine.

[0008] Furthermore, the mesh size of the frit is 300-700 meshes; the penetrant is one or more of cocamidopropyl betaine, polyoxyethylene alkanolamide, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfate.

[0009] Furthermore, the preparation of the antimicrobial protein-coupled antifouling coating comprises the following steps:

[0010] S1. Preparation of conjugate 1: first dissolving the antibacterial protein in DMSO, then adding deionized water to obtain an antibacterial protein solution; dissolving N-succinimidyl-3-(2-pyridyldithio) propionate in DMSO to obtain a DMSO solution of SPDP; adding the DMSO solution of SPDP to the antibacterial protein solution, stirring at room temperature, dialysis purification with deionized water, and freeze-drying to obtain a pure conjugate 1;

[0011] S2, preparing conjugate 2: dissolving conjugate 1 and polyethylene glycol methacrylate in deionized water, bubbling under argon to obtain a mixed solution 1, adding a cupric chloride solution, sodium ascorbate and HMTETA ligand into another flask, and then mixing the solutions, reacting at room temperature, dialysis purification, and lyophilizing to obtain conjugate 2;

[0012] S3, preparing the conjugate 2 into a conjugate 2 solution and mixing it with ethanol to obtain an antimicrobial protein-conjugated antifouling coating.

[0013] Furthermore, in S1, the antibacterial protein is lactoperoxidase or lysostaphin, the concentration of the antibacterial protein solution is 4-6 mg / mL, the concentration of the DMSO solution of N-succinimidyl-3-(2-pyridyldithio)propionate is 140-155 mg / mL, the volume ratio of the antibacterial protein solution and the DMSO solution of SPDP is 200:1, and the mixture is stirred at room temperature for 2-3 hours.

[0014] Furthermore, in S2, the number of ethylene glycol units in the PEG chain of polyethylene glycol methacrylate is 5, the weight ratio of conjugate 1 to polyethylene glycol methacrylate is 15:(26-28), the concentrations of conjugate 1 and polyethylene glycol methacrylate are 1.3-1.5 mg / mL and 2.7-2.8 mg / mL, respectively, and bubbling under argon is performed for 45-50 min; the volume ratio of mixed solution 1, copper chloride solution, sodium ascorbate and HMTETA ligand is 20000:(2350-2450):(100-120):(35-38), the copper chloride solution is 50 mM, the sodium ascorbate is 100 mM, and the reaction is carried out at room temperature for 2-3 h.

[0015] Furthermore, in S3, the concentration of the conjugate 2 solution is 2-2.2 mg / mL, the concentration of ethanol is 40-50%, the conjugate 2 solution and ethanol are mixed in equal volumes, and reacted at room temperature for 10-20 minutes.

[0016] The present invention also provides a method for preparing soft-polished anti-fouling tiles, comprising the following steps:

[0017] (1) preparing the green body layer: weighing corresponding weight portions of raw materials according to the formula of the green body layer, adding water, and putting them into a ball mill for ball milling to obtain a green body slurry, and then sieving to remove iron, spray granulation, aging and homogenization, pressing and forming, and drying to obtain the green body layer;

[0018] (2) preparing the bottom glaze layer: weighing corresponding weight portions of raw materials according to the formula of the bottom glaze layer, adding water, putting into a ball mill for ball milling, and then removing iron to obtain a bottom glaze slurry, applying the bottom glaze on the green body to obtain the bottom glaze layer;

[0019] (3) preparing a pattern layer: adding a pattern on the base glaze layer to obtain a pattern layer;

[0020] (4) preparing a protective glaze layer: weighing raw materials in corresponding weight parts according to the formula of the protective glaze, adding water, putting them into a ball mill for ball milling, and then removing iron to obtain a protective glaze slurry, and applying the protective glaze on the pattern layer to obtain a protective glaze layer;

[0021] (5) Firing: The ceramic tile body is obtained by placing the ceramic tile with the base glaze layer, pattern layer and protective glaze layer into a kiln for sintering;

[0022] (6) Polishing: using a resin abrasive disc of a first mesh number to perform coarse grinding and polishing on the ceramic tile body to obtain a coarse polished product, then using a resin abrasive disc of a second mesh number to perform medium grinding and polishing to obtain a medium polished product, and finally using a fiber brush to perform soft grinding and polishing on the tile surface to obtain a soft polished product;

[0023] (7) Cleaning: Wash the surface of the soft polished product with water and dry it to obtain a clean and dry soft polished product;

[0024] (8) Spraying the antimicrobial protein-coupled antifouling coating: spraying the antimicrobial protein-coupled antifouling coating evenly on the surface of a clean and dry soft-polished product, and after film formation, obtaining a soft-polished antifouling tile pre-finished product;

[0025] (9) Soak the soft-polished anti-fouling tile pre-finished product in a glutaraldehyde solution, and after the reaction is completed, wash with water and dry it to obtain the soft-polished anti-fouling tile.

[0026] Furthermore, in step (1), step (2) and step (4), the water addition ratio is 25-35%; in step (3), the pattern is added by inkjet printing, screen printing or rubber roller printing; in step (4), a protective glaze is applied on the surface of the pattern layer by glazing, spraying or dipping, and the weight is controlled at 200-400 grams per square meter; preferably, the protective glaze is applied by glazing; in step (5), the firing temperature is 1100-1280°C, and the firing time is controlled at 35-60 minutes; in step (6), the first mesh size is 100-1200°C; ... The mesh number of the resin grinding disc is 100-400, the rotation speed of the first mesh number resin grinding disc is 800-2000rpm, and the rough grinding and polishing pressure is 0.2-0.5MPa; the mesh number of the second mesh number resin grinding disc is 600-1000, the rotation speed of the second mesh number resin grinding disc is 1500-3000rpm, and the medium grinding and polishing pressure is 0.1-0.6MPa; in step (8), the antifouling coating is sprayed for 20-30min to form a film; in step (9), the concentration of the glutaraldehyde solution is 1%, and the reaction time is 30-50min.

[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0028] 1. The present invention can reduce the mining of primary minerals, reduce production costs, and reduce the pollution of waste to the environment by using ceramic recycled materials as one of the main raw materials for the body layer. The serpentine is further modified by heat treatment and chemical treatment. During the heat treatment process, Mg, Si, O, etc. in the serpentine will be rearranged to form a more stable structure. Sodium aluminate solution is added to fill the pores of the serpentine. Aluminum ions can react with the silicon-oxygen tetrahedral structure in the serpentine to form a more stable chemical bond, thereby improving the hardness and wear resistance of the serpentine, achieving the purpose of improving the hardness and wear resistance of the ceramic tile; after being applied to the hierarchical structure of the body layer, the base glaze layer, the pattern layer, the protective glaze layer and the antibacterial protein-coupled antifouling coating, the hardness and wear resistance of the ceramic tile can be significantly improved.

[0029] 2. The present invention combines N-succinimidyl-3-(2-pyridyldithio) propionate with antimicrobial protein, wherein the active ester group reacts with the amine group of the antimicrobial protein to form a stable amide bond, thereby improving the stability of the antimicrobial protein and helping to maintain the biological activity of the antimicrobial protein; the conjugate 1 is then combined with polyethylene glycol methacrylate to introduce polyethylene glycol chains to increase the hydrophilicity and biocompatibility of the antimicrobial protein; and finally, an ethanol solution is added to improve the fluidity of the coating, which not only makes the spraying more uniform, but also improves the adhesion of the coating on the surface of the tile. The coating can effectively resist various stains, including water-based and oily substances, thereby enhancing the anti-fouling performance of the tile. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 It is a schematic diagram of the hierarchical structure of a soft-polished anti-fouling tile of the present invention;

[0032] Wherein, the reference numerals are:

[0033] 1: body layer; 2: base glaze layer; 3: pattern layer; 4: protective glaze layer; 5: antibacterial protein coupled antifouling coating. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1: See Figure 1 As shown, the present embodiment discloses a soft-polished anti-fouling tile, which comprises, from bottom to top, a body layer 1, a base glaze layer 2, a pattern layer 3, a protective glaze layer 4 and an antibacterial protein-coupled anti-fouling coating 5; the body layer comprises the following raw materials by weight: 42kg of ceramic recycled material, 45kg of kaolin, 35kg of dolomite, 28kg of wollastonite, 32kg of albite, 16kg of potassium feldspar, 30kg of high-alumina clay, and 20kg of modified serpentine; the base glaze layer comprises the following raw materials by weight: 22kg of albite, 12kg of potassium feldspar, 12kg of quartz sand, 3kg of magnesium oxide, and 4kg of aluminum oxide; the protective glaze layer comprises the following raw materials by weight: 35kg of frit, 52kg of suspended glue, 3kg of polyethylene wax emulsion, 2kg of cocamidopropyl betaine, 6kg of albite, 6kg of potassium feldspar, 5kg of quartz, 2kg of burnt talc, 3kg of barium carbonate, 5kg of calcined zinc oxide, and 3kg of kaolin.

[0036] Specifically, the ceramic recycling material includes the following raw materials by weight percentage: 50wt% ceramic waste, 20wt% clay, 20wt% quartz sand, 5wt% feldspar and 5wt% additives; the additives are talc, dolomite, borax, boric acid, iron oxide and aluminum oxide mixed in a mass ratio of 4:4:2:2:1:1; when preparing the modified serpentine, the serpentine is crushed to 50μm, heated to 470℃ at a speed of 2℃ / min, kept warm for 70min, and then heated to 1100℃ at a speed of 1.2℃ / min, and then added with a sodium aluminate solution with a concentration of 80mg / L equal to the weight of the serpentine, mixed evenly, kept warm for 40min, and naturally cooled to room temperature to obtain the modified serpentine. The mesh number of the frit is 300 mesh.

[0037] Specifically, the preparation of the antimicrobial protein-coupled antifouling coating comprises the following steps:

[0038] S1. Preparation of conjugate 1: Dissolve 40 mg lactoperoxidase and 40 mg lysostaphin in DMSO, then add deionized water to 20 mL to obtain an antibacterial protein solution; dissolve 14 mg N-succinimidyl-3-(2-pyridyldithio)propionate in 0.1 mL DMSO to obtain a DMSO solution of SPDP; add the DMSO solution of SPDP to the antibacterial protein solution, stir at room temperature for 2 h, dialyze and purify with deionized water, and lyophilize to obtain a pure conjugate 1;

[0039] S2. Preparation of conjugate 2: 30 mg of conjugate 1 and 52 mg of polyethylene glycol methacrylate were dissolved in deionized water to 20 mL, wherein the number of ethylene glycol units in the PEG chain of polyethylene glycol methacrylate was 5, and the mixture was bubbled under argon for 45 min to obtain a mixed solution 1. In another flask, 2.35 mL of 50 mM copper chloride solution was added, and then 100 μL of 100 mM sodium ascorbate and 35 μL of HMTETA ligand were added. The solutions were then mixed and reacted at room temperature for 2 h. After purification by dialysis, the mixture was lyophilized to obtain conjugate 2.

[0040] S3. After preparing a 2 mg / mL solution of the conjugate, add an equal volume of 40% ethanol and react at room temperature for 10 minutes to obtain an antimicrobial protein-conjugated antifouling coating.

[0041] This embodiment also discloses a method for preparing soft-polished anti-fouling tiles, comprising the following steps:

[0042] (1) preparing the green body layer: weighing the raw materials according to the formula of the green body layer, adding water at a ratio of 25%, putting the raw materials into a ball mill for ball milling to obtain a green body slurry, and then sieving to remove iron, spray granulation, aging and homogenization, pressing and forming, and drying to obtain the green body layer;

[0043] (2) preparing the bottom glaze layer: weighing corresponding weights of raw materials according to the formula of the bottom glaze layer, adding water at a ratio of 25%, putting the raw materials into a ball mill for ball milling, and then removing iron to obtain a bottom glaze slurry, applying the bottom glaze on the green body to obtain the bottom glaze layer;

[0044] (3) preparing a pattern layer: adding a pattern on the base glaze layer by inkjet printing to obtain a pattern layer;

[0045] (4) preparing a protective glaze layer: weighing corresponding weights of raw materials according to the formula of the protective glaze, adding water at a ratio of 25%, putting the raw materials into a ball mill for ball milling, and then removing iron to obtain a protective glaze slurry, applying the protective glaze on the pattern layer, applying the protective glaze on the surface of the pattern layer by dipping, and controlling the weight to be 200 g per square meter to obtain a protective glaze layer;

[0046] (5) Firing: Place the base glaze layer, pattern layer, and protective glaze layer into a kiln for sintering at a temperature of 1100°C and a firing time of 35 minutes to obtain a ceramic tile body;

[0047] (6) Polishing: using a first resin abrasive disc with a mesh size of 100 to 400, the ceramic tile body is coarsely ground and polished with mesh sizes of 100, 200, 300, and 400, respectively, at a coarse grinding and polishing speed of 1000 rpm and a coarse grinding and polishing pressure of 0.2 MPa to obtain a coarse polished product, then using a second resin abrasive disc with a mesh size of 1000 to perform medium grinding and polishing, at a medium grinding and polishing speed of 1500 rpm and a medium grinding and polishing pressure of 0.3 MPa to obtain a medium polished product, and finally using a fiber brush to perform soft grinding and polishing on the tile surface to obtain a soft polished product;

[0048] (7) Cleaning: Wash the surface of the soft polished product with water and dry it to obtain a clean and dry soft polished product;

[0049] (8) Spraying the antimicrobial protein-coupled antifouling coating: spray the antimicrobial protein-coupled antifouling coating evenly on the surface of the clean and dry soft-polished product, and after film formation for 20 minutes, obtain a soft-polished antifouling tile pre-finished product;

[0050] (9) The soft-polished anti-fouling tile pre-finished product is immersed in a 1% glutaraldehyde solution and reacted for 30 minutes. After washing with water and drying, the soft-polished anti-fouling tile is obtained.

[0051] Embodiment 2: This embodiment discloses a soft-polished anti-fouling tile, see Figure 1 As shown, the present embodiment discloses a soft-polished anti-fouling tile, which comprises, from bottom to top, a body layer 1, a base glaze layer 2, a pattern layer 3, a protective glaze layer 4 and an antibacterial protein-coupled anti-fouling coating 5; the body layer comprises the following raw materials by weight: 44kg of ceramic recycled material, 40kg of kaolin, 33kg of dolomite, 27kg of wollastonite, 28kg of albite, 14kg of potassium feldspar, 25kg of high-alumina clay, and 23kg of modified serpentine; the base glaze layer comprises the following raw materials by weight: 30kg of albite, 22kg of potassium feldspar, 21kg of quartz sand, 4kg of magnesium oxide, and 5kg of aluminum oxide; the protective glaze layer comprises the following raw materials by weight: 38kg of frit, 60kg of suspended glue, 4kg of polyethylene wax emulsion, 1kg of cocamidopropyl betaine, 7kg of albite, 7kg of potassium feldspar, 8kg of quartz, 3kg of burnt talc, 2kg of barium carbonate, 4kg of calcined zinc oxide, and 5kg of kaolin.

[0052] Specifically, the ceramic recycling material includes the following raw materials by weight percentage: 54wt% ceramic waste, 25wt% clay, 10wt% quartz sand, 5wt% feldspar and 6wt% additives; the additives are talc, dolomite, borax, boric acid and alumina mixed in a mass ratio of 4:3:1:1:1; when preparing the modified serpentine, the serpentine is crushed to 60μm, heated to 480℃ at a rate of 2℃ / min, kept warm for 50min, and then heated to 1150℃ at a rate of 1.5℃ / min, and then a sodium aluminate solution with a concentration of 85mg / L equal to the weight of the serpentine is added, mixed evenly, kept warm for 40min, and naturally cooled to room temperature to obtain the modified serpentine. The mesh number of the frit is 400 mesh.

[0053] Specifically, the preparation of the antimicrobial protein-coupled antifouling coating comprises the following steps:

[0054] S1. Preparation of conjugate 1: Dissolve 50 mg lactoperoxidase and 50 mg lysostaphin in DMSO, then add deionized water to 20 mL to obtain an antibacterial protein solution; dissolve 14.5 mg N-succinimidyl-3-(2-pyridyldithio)propionate in 0.1 mL DMSO to obtain a DMSO solution of SPDP; add the DMSO solution of SPDP to the antibacterial protein solution, stir at room temperature for 2 h, dialyze and purify with deionized water, and lyophilize to obtain a pure conjugate 1;

[0055] S2. Preparation of conjugate 2: 30 mg of conjugate 1 and 53 mg of polyethylene glycol methacrylate were dissolved in deionized water to 20 mL, wherein the number of ethylene glycol units in the PEG chain of polyethylene glycol methacrylate was 5, and the mixture was bubbled under argon for 45 to 50 min to obtain a mixed solution 1. In another flask, 2.37 mL of 50 mM copper chloride solution was added, and then 110 μL of 100 mM sodium ascorbate and 37 μL of HMTETA ligand were added. The solutions were then mixed and reacted at room temperature for 2 h. After purification by dialysis, the mixture was lyophilized to obtain conjugate 2.

[0056] S3. After preparing a 2.1 mg / mL solution of the conjugate, add an equal volume of 42% ethanol solution and react at room temperature for 15 minutes to obtain an antimicrobial protein-conjugated antifouling coating.

[0057] This embodiment also discloses a method for preparing soft-polished anti-fouling tiles, comprising the following steps:

[0058] (1) Preparation of the green body layer: weighing corresponding weights of raw materials according to the formula of the green body layer, adding water at a ratio of 27%, putting into a ball mill for ball milling to obtain a green body slurry, and then sieving to remove iron, spray granulation, aging and homogenization, pressing and forming, and drying to obtain the green body layer;

[0059] (2) preparing the bottom glaze layer: weighing corresponding weights of raw materials according to the formula of the bottom glaze layer, adding water at a ratio of 27%, putting the raw materials into a ball mill for ball milling, and then removing iron to obtain a bottom glaze slurry, applying the bottom glaze on the green body to obtain the bottom glaze layer;

[0060] (3) preparing a pattern layer: adding a pattern on the base glaze layer by screen printing to obtain a pattern layer;

[0061] (4) preparing a protective glaze layer: weighing corresponding weights of raw materials according to the formula of the protective glaze, adding water at a ratio of 27%, putting the raw materials into a ball mill for ball milling, and then removing iron to obtain a protective glaze slurry, applying the protective glaze on the pattern layer, and applying the protective glaze on the surface of the pattern layer by dipping, with the weight controlled at 250 g per square meter, to obtain a protective glaze layer;

[0062] (5) Firing: Place the base glaze layer, pattern layer and protective glaze layer into a kiln for sintering at a temperature of 1150°C and a firing time of 45 minutes to obtain a ceramic tile body;

[0063] (6) Polishing: using a first resin abrasive disc with a mesh size of 100 to 400, and respectively using resin abrasive discs with mesh sizes of 100, 300, and 400 to perform coarse grinding and polishing on the ceramic tile body, the coarse grinding and polishing speed is 1050 rpm, the coarse grinding and polishing pressure is 0.3 MPa, and a coarse polished product is obtained; then using a second resin abrasive disc with a mesh size of 700 to perform medium grinding and polishing, the medium grinding and polishing speed is 1800 rpm, the medium grinding and polishing pressure is 0.2 MPa, and a medium polished product is obtained; finally, a fiber brush is used to perform soft grinding and polishing on the tile surface to obtain a soft polished product;

[0064] (7) Cleaning: Wash the surface of the soft polished product with water and dry it to obtain a clean and dry soft polished product;

[0065] (8) Spraying the antimicrobial protein-coupled antifouling coating: spray the antimicrobial protein-coupled antifouling coating evenly on the surface of a clean and dry soft-polished product, and after 25 minutes of film formation, obtain a soft-polished antifouling tile pre-finished product;

[0066] (9) The soft-polished anti-fouling tile pre-finished product is immersed in a 1% glutaraldehyde solution and reacted for 40 minutes. After washing with water and drying, the soft-polished anti-fouling tile is obtained.

[0067] Embodiment 3: This embodiment discloses a soft-polished anti-fouling tile, see Figure 1As shown, this embodiment discloses a soft-polished anti-fouling tile, which includes a body layer 1, a base glaze layer 2, a pattern layer 3, a protective glaze layer 4 and an antibacterial protein-coupled anti-fouling coating 5 from bottom to top; the body layer includes the following raw materials by weight: 44kg of ceramic recycled materials, 45kg of kaolin, 35kg of dolomite, 26kg of wollastonite, 25kg of albite, 12kg of potassium feldspar, 25kg of high-alumina clay, and 25kg of modified serpentine; the base glaze layer includes by weight: The following raw materials: 30kg of albite, 21kg of potassium feldspar, 23kg of quartz sand, 4kg of magnesium oxide, and 6kg of aluminum oxide; the protective glaze layer includes the following raw materials by weight: 40kg of frit, 55kg of suspended glue, 4kg of polyethylene wax emulsion, 1kg of polyoxyethylene alkanolamide, 1kg of sodium dodecylbenzene sulfonate, 8kg of albite, 8kg of potassium feldspar, 10kg of quartz, 4kg of burnt talc, 3kg of barium carbonate, 4kg of calcined zinc oxide, and 3kg of kaolin.

[0068] Specifically, the ceramic recycling material includes the following raw materials by weight percentage: 60wt% ceramic waste, 10wt% clay, 15wt% quartz sand, 5wt% feldspar and 10wt% additives; the additives are talc, dolomite, borax, boric acid, iron oxide and aluminum oxide mixed in a mass ratio of 3:4:2:2:1:1; when preparing the modified serpentine, the serpentine is crushed to 70μm, heated to 490℃ at a speed of 3℃ / min, kept warm for 70min, and then heated to 1180℃ at a speed of 1.9℃ / min, and then a sodium aluminate solution with a concentration of 92mg / L equal to the weight of the serpentine is added, mixed evenly, kept warm for 60min, and naturally cooled to room temperature to obtain the modified serpentine. The mesh number of the frit is 600 mesh.

[0069] Specifically, the preparation of the antimicrobial protein-coupled antifouling coating comprises the following steps:

[0070] S1. Preparation of conjugate 1: Dissolve 60 mg lactoperoxidase and 60 mg lysostaphin in DMSO, then add deionized water to 20 mL to obtain an antibacterial protein solution; dissolve 15 g N-succinimidyl-3-(2-pyridyldithio)propionate in 0.1 mL DMSO to obtain a DMSO solution of SPDP; add the DMSO solution of SPDP to the antibacterial protein solution, stir at room temperature for 3 h, dialyze and purify with deionized water, and lyophilize to obtain a pure conjugate 1;

[0071] S2. Preparation of conjugate 2: 30 mg of conjugate 1 and 55 mg of polyethylene glycol methacrylate were dissolved in deionized water to 20 mL, wherein the number of ethylene glycol units in the PEG chain of polyethylene glycol methacrylate was 5, and the mixture was bubbled under argon for 50 min to obtain a mixed solution 1. In another flask, 2.4 mL of 50 mM copper chloride solution was added, and then 110 μL of 100 mM sodium ascorbate and 38 μL of HMTETA ligand were added. The solutions were then mixed and reacted at room temperature for 2 to 3 h. After purification by dialysis, the mixture was lyophilized to obtain conjugate 2.

[0072] S3. After preparing a 2.2 mg / mL solution of the conjugate, add an equal volume of 46% ethanol and react at room temperature for 20 minutes to obtain an antimicrobial protein-conjugated antifouling coating.

[0073] This embodiment also discloses a method for preparing soft-polished anti-fouling tiles, comprising the following steps:

[0074] (1) preparing the green body layer: weighing the raw materials according to the formula of the green body layer, adding water at a ratio of 30%, putting the raw materials into a ball mill for ball milling to obtain a green body slurry, and then sieving to remove iron, spray granulation, aging and homogenization, pressing and forming, and drying to obtain the green body layer;

[0075] (2) preparing the bottom glaze layer: weighing the corresponding weight of raw materials according to the formula of the bottom glaze layer, adding water, the water addition ratio is 30%, putting into a ball mill for ball milling, and then removing iron to obtain the bottom glaze slurry, applying the bottom glaze on the blank to obtain the bottom glaze layer;

[0076] (3) preparing a pattern layer: adding a pattern on the base glaze layer by using a rubber roller printing method to obtain a pattern layer;

[0077] (4) preparing a protective glaze layer: weighing corresponding weights of raw materials according to the formula of the protective glaze, adding water at a ratio of 30%, putting the raw materials into a ball mill for ball milling, and then removing iron to obtain a protective glaze slurry, applying the protective glaze on the pattern layer, and applying the protective glaze on the surface of the pattern layer by pouring glaze, with the weight controlled at 400 g per square meter, to obtain a protective glaze layer;

[0078] (5) Firing: Place the base glaze layer, pattern layer, and protective glaze layer into a kiln for sintering at a temperature of 1200°C and a firing time of 60 minutes to obtain a ceramic tile body;

[0079] (6) Polishing: using a first resin abrasive disc with a mesh size of 100 to 400, and respectively using resin abrasive discs with mesh sizes of 100, 200, and 400 to perform coarse grinding and polishing on the ceramic tile body, the coarse grinding and polishing speed is 1500 rpm, the coarse grinding and polishing pressure is 0.4 MPa, and a coarse polished product is obtained. Then, using a second resin abrasive disc with a mesh size of 800 to perform medium grinding and polishing, the medium grinding and polishing speed is 2000 rpm, the medium grinding and polishing pressure is 0.5 MPa, and a medium polished product is obtained. Finally, a fiber brush is used to perform soft grinding and polishing on the tile surface to obtain a soft polished product.

[0080] (7) Cleaning: Wash the surface of the soft polished product with water and dry it to obtain a clean and dry soft polished product;

[0081] (8) Spraying the antimicrobial protein-coupled antifouling coating: spray the antimicrobial protein-coupled antifouling coating evenly on the surface of the clean and dry soft polished product, and after film formation for 30 minutes, obtain the soft polished antifouling tile pre-finished product;

[0082] (9) The soft-polished anti-fouling tile pre-finished product is immersed in a 1% glutaraldehyde solution and reacted for 50 minutes. After washing with water and drying, the soft-polished anti-fouling tile is obtained.

[0083] Embodiment 4: This embodiment discloses a soft polishing anti-fouling tile, see Figure 1 As shown, this embodiment discloses a soft-polished anti-fouling tile, which comprises, from bottom to top, a body layer 1, a base glaze layer 2, a pattern layer 3, a protective glaze layer 4 and an antibacterial protein coupled anti-fouling coating 5; the body layer comprises the following raw materials by weight: 46kg of ceramic recycled material, 45kg of kaolin, 32kg of dolomite, 26kg of wollastonite, 25kg of albite, 12kg of potassium feldspar, 15kg of high-alumina clay, and 25kg of modified serpentine; the base glaze layer comprises by weight: The following raw materials: 22kg of albite, 26kg of potassium feldspar, 25kg of quartz sand, 6kg of magnesium oxide, and 2kg of aluminum oxide; the protective glaze layer includes the following raw materials by weight: 43kg of frit, 62kg of suspended glue, 4kg of polyethylene wax emulsion, 1kg of cocamidopropyl betaine, 1kg of sodium lauryl sulfate, 6-8kg of albite, 6kg of potassium feldspar, 7kg of quartz, 3kg of burnt talc, 3kg of barium carbonate, 4kg of calcined zinc oxide, and 6kg of kaolin.

[0084] Specifically, the ceramic recycling material includes the following raw materials by weight percentage: 60wt% ceramic waste, 5wt% clay, 20wt% quartz sand, 10wt% feldspar and 5wt% additives; the additives are talc, dolomite, boric acid and alumina mixed in a mass ratio of 3:2:1:1; when preparing the modified serpentine, the serpentine is crushed to 80μm, heated to 500℃ at a rate of 3℃ / min, kept warm for 70min, and then heated to 1200℃ at a rate of 2.0℃ / min, and then a sodium aluminate solution with a concentration of 95mg / L equal to the weight of the serpentine is added, mixed evenly, kept warm for 60min, and naturally cooled to room temperature to obtain the modified serpentine. The mesh number of the frit is 700 mesh.

[0085] Specifically, the preparation of the antimicrobial protein-coupled antifouling coating comprises the following steps:

[0086] S1. Preparation of conjugate 1: Dissolve 60 mg lactoperoxidase and 60 mg lysostaphin in DMSO, then add deionized water to 20 mL to obtain an antibacterial protein solution; dissolve 15.5 mg N-succinimidyl-3-(2-pyridyldithio)propionate in 0.1 mL DMSO to obtain a DMSO solution of SPDP; add the DMSO solution of SPDP to the antibacterial protein solution, stir at room temperature for 3 h, dialyze and purify with deionized water, and lyophilize to obtain a pure conjugate 1;

[0087] S2. Preparation of conjugate 2: 30 mg of conjugate 1 and 56 mg of polyethylene glycol methacrylate were dissolved in deionized water to 20 mL, wherein the number of ethylene glycol units in the PEG chain of polyethylene glycol methacrylate was 5, and the mixture was bubbled under argon for 50 min to obtain a mixed solution 1. In another flask, 2.4 mL of 50 mM copper chloride solution was added, and then 120 μL of 100 mM sodium ascorbate and 38 μL of HMTETA ligand were added. The solutions were then mixed and reacted at room temperature for 3 h. After purification by dialysis, the mixture was lyophilized to obtain conjugate 2.

[0088] S3. After preparing a 2.2 mg / mL solution of the conjugate, add an equal volume of 50% ethanol and react at room temperature for 20 minutes to obtain an antimicrobial protein-conjugated antifouling coating.

[0089] This embodiment also discloses a method for preparing soft-polished anti-fouling tiles, comprising the following steps:

[0090] (1) Preparation of the green body layer: weighing the corresponding weight of raw materials according to the formula of the green body layer, adding water, the water addition ratio is 35%, putting into a ball mill for ball milling to obtain a green body slurry, and then sieving to remove iron, spray granulation, aging and homogenization, pressing and forming, and drying to obtain the green body layer;

[0091] (2) preparing the bottom glaze layer: weighing the corresponding weight of raw materials according to the formula of the bottom glaze layer, adding water, the water addition ratio is 35%, putting into a ball mill for ball milling, and then removing iron to obtain the bottom glaze slurry, applying the bottom glaze on the green body to obtain the bottom glaze layer;

[0092] (3) preparing a pattern layer: adding a pattern on the base glaze layer by inkjet printing to obtain a pattern layer;

[0093] (4) preparing a protective glaze layer: weighing corresponding weights of raw materials according to the formula of the protective glaze, adding water at a ratio of 35%, putting the raw materials into a ball mill for ball milling, and then removing iron to obtain a protective glaze slurry, applying the protective glaze on the pattern layer, applying the protective glaze on the surface of the pattern layer by pouring glaze, and controlling the weight to be 400 g per square meter to obtain a protective glaze layer;

[0094] (5) Firing: Place the base glaze layer, pattern layer, and protective glaze layer into a kiln for sintering at a temperature of 1280°C and a firing time of 60 minutes to obtain a ceramic tile body;

[0095] (6) Polishing: using a first resin abrasive disc with a mesh size of 100 to 400, and using resin abrasive discs with mesh sizes of 100, 200, 250, and 400 respectively, to perform coarse grinding and polishing on the ceramic tile blank, the coarse grinding and polishing speed is 2000 rpm, the coarse grinding and polishing pressure is 0.5 MPa, to obtain a coarse polished product, then using a second resin abrasive disc with a mesh size of 1000 to perform medium grinding and polishing, the medium grinding and polishing speed is 3000 rpm, the medium grinding and polishing pressure is 0.6 MPa, to obtain a medium polished product, and finally using a fiber brush to perform soft grinding and polishing on the tile surface to obtain a soft polished product;

[0096] (7) Cleaning: Wash the surface of the soft polished product with water and dry it to obtain a clean and dry soft polished product;

[0097] (8) Spraying the antimicrobial protein-coupled antifouling coating: spray the antimicrobial protein-coupled antifouling coating evenly on the surface of the clean and dry soft polished product, and after film formation for 30 minutes, obtain the soft polished antifouling tile pre-finished product;

[0098] (9) The soft-polished anti-fouling tile pre-finished product is immersed in a 1% glutaraldehyde solution and reacted for 50 minutes. After washing with water and drying, the soft-polished anti-fouling tile is obtained.

[0099] Comparative Example 1

[0100] Comparative Example 1 Compared with Example 3, in the preparation process of the soft-polished anti-fouling ceramic tile in Comparative Example 1, no antibacterial protein-coupled anti-fouling coating was added, and other conditions remained unchanged.

[0101] Comparative Example 2

[0102] Comparative Example 2 Compared with Example 3, in the preparation process of the soft-polished anti-fouling ceramic tile, in Comparative Example 2, the antibacterial protein is directly added without coupling to prepare the anti-fouling coating, and other conditions remain unchanged.

[0103] Comparative Example 3

[0104] Comparative Example 3 Compared with Example 3, in the preparation process of the soft-polished anti-fouling ceramic tile in Comparative Example 3, no modified serpentine is added, and unmodified serpentine is added as a raw material replacement, and other conditions remain unchanged.

[0105] Experimental example

[0106] 9 tiles of each of Examples 1 to 4 and Comparative Examples 1 to 3 were randomly selected, with a size of 30×30 cm, and randomly divided into 2 groups for performance testing, one group for antibacterial experiments, and the other group for soft light effect, wear resistance, and antifouling performance tests.

[0107] 1. Antibacterial performance testing

[0108] With reference to GB / T9266-2009, the antibacterial performance of the tiles obtained in Examples 1 to 4 and Comparative Examples 1 to 3 was tested by the Microbiological Analysis and Testing Center. The test results are shown in Table 1.

[0109] Table 1 Antibacterial performance test results

[0110]

[0111] According to the test results in Table 1, it can be seen that the soft-polished antifouling tiles prepared in Examples 1 to 4 of the present invention significantly enhance the inhibitory effect on Escherichia coli and Staphylococcus aureus, that is, improve the antibacterial properties of the tiles. By comparing Comparative Example 1 with Examples 1 to 4, it can be seen that adding antibacterial protein-coupled antifouling coatings can significantly enhance the antibacterial properties of tiles. By comparing Comparative Example 2 with Examples 1 to 4, it can be seen that coupling treatment of antibacterial proteins can improve the stability of the antibacterial properties of tiles and achieve a sustained antibacterial effect.

[0112] 2. Soft light effect, wear resistance and anti-fouling performance test

[0113] The glossiness was measured by a photometer, the strength was measured according to GB / T 4100-2015, and the antifouling grade was measured according to GB / T3810.14-2016. The ceramic tiles obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to performance tests, and the test results are shown in Table 2.

[0114] Table 2 Test results of soft light effect, wear resistance and antifouling performance

[0115] Glossiness / (GU) Strength / (MPa) Antifouling grade Embodiment 1 31 41.41 Level 5 Embodiment 2 31 41.65 Level 5 Embodiment 3 32 41.74 Level 5 Embodiment 4 32 41.22 Level 5 Comparative Example 1 58 41.62 Level 2 Comparative Example 2 46 41.58 Level 2 Comparative Example 3 33 20.76 Level 5

[0116] According to the test results in Table 2, it can be seen from the comparison between Comparative Example 1 and Examples 1 to 4 that the addition of the antimicrobial protein-coupled antifouling coating has an enhanced soft light effect of the tile, which may be related to the addition of the antimicrobial protein-coupled antifouling coating on the outer surface of the tile. It can be seen from the comparison between Comparative Example 3 and Examples 1 to 4 that when preparing soft light antifouling tiles, adding modified serpentine can improve the strength of the tiles and enhance the wear resistance of the tiles.

[0117] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0118] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A soft-polished anti-fouling tile, characterized in that: The invention comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer, a protective glaze layer and an antibacterial protein coupled antifouling coating; the body layer comprises the following raw materials in parts by weight: 42 to 46 parts of ceramic recycled materials, 20 to 45 parts of kaolin, 32 to 35 parts of dolomite, 26 to 28 parts of wollastonite, 25 to 32 parts of albite, 12 to 16 parts of potassium feldspar, 15 to 30 parts of high-alumina clay and 20 to 25 parts of modified serpentine; the base glaze layer comprises the following raw materials in parts by weight: 2 2-35 parts, potassium feldspar 12-26 parts, quartz sand 12-25 parts, magnesium oxide 3-6 parts and aluminum oxide 2-8 parts; the protective glaze layer includes the following raw materials by weight: 35-43 parts of frit, 52-65 parts of suspended glue, 3-6 parts of polyethylene wax emulsion, 1-2 parts of penetrant, 6-8 parts of sodium feldspar, 6-8 parts of potassium feldspar, 5-10 parts of quartz, 2-4 parts of burned talc, 2-3 parts of barium carbonate, 4-5 parts of calcined zinc oxide and 3-8 parts of kaolin.

2. The soft-polished anti-fouling tile according to claim 1, characterized in that: The ceramic recycling material comprises the following raw materials in parts by weight: 50-60wt% of ceramic waste, 5-30wt% of clay, 5-20wt% of quartz sand, 5-10wt% of feldspar and 5-10wt% of additives; the additives are one or more of talc, dolomite, borax, boric acid, iron oxide and aluminum oxide.

3. The soft-polished anti-fouling tile according to claim 1, characterized in that: When preparing the modified serpentine, the serpentine is crushed to 50-80 μm, heated to a temperature of 470-500° C. at a rate of 2-3° C. / min, kept warm for 50-70 minutes, and then heated to 1100-1200° C. at a rate of 1.2-2.0° C. / min, and then a sodium aluminate solution with a concentration of 80-95 mg / L and an equal weight to that of the serpentine is added, mixed evenly, kept warm for 40-60 minutes, and naturally cooled to room temperature to obtain the modified serpentine.

4. The soft-polished anti-fouling tile according to claim 1, characterized in that: The mesh number of the frit is 300-700 meshes; the penetrant is one or more of cocamidopropyl betaine, oxyethylene alkanolamide, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfate.

5. The soft-polished anti-fouling tile according to claim 1, characterized in that: The preparation of the antimicrobial protein-coupled antifouling coating comprises the following steps: S1. Preparation of conjugate 1: first dissolving the antibacterial protein in DMSO, then adding deionized water to obtain an antibacterial protein solution; dissolving N-succinimidyl-3-(2-pyridyldithio) propionate in DMSO to obtain a DMSO solution of SPDP; adding the DMSO solution of SPDP to the antibacterial protein solution, stirring at room temperature, dialysis purification with deionized water, and freeze-drying to obtain a pure conjugate 1; S2, preparing conjugate 2: dissolving conjugate 1 and polyethylene glycol methacrylate in deionized water, bubbling under argon to obtain a mixed solution 1, adding a cupric chloride solution, sodium ascorbate and HMTETA ligand into another flask, and then mixing the solutions, reacting at room temperature, dialysis purification, and lyophilizing to obtain conjugate 2; S3. Conjugate 2 is prepared into a conjugate 2 solution and then mixed with ethanol to obtain an antimicrobial protein-conjugated antifouling coating.

6. The soft-polished anti-fouling tile according to claim 5, characterized in that: In S1, the antibacterial proteins are lactoperoxidase and lysostaphin, the concentration of the antibacterial protein solution is 4-6 mg / mL, the concentration of the DMSO solution of N-succinimidyl-3-(2-pyridyldithio)propionate is 140-155 mg / mL, the volume ratio of the antibacterial protein solution and the DMSO solution of SPDP is 200:1, and the mixture is stirred at room temperature for 2-3 hours.

7. The soft-polished anti-fouling tile according to claim 5, characterized in that: In S2, the number of ethylene glycol units in the PEG chain of polyethylene glycol methacrylate is 5, the weight ratio of conjugate 1 to polyethylene glycol methacrylate is 15:(26-28), the concentrations of conjugate 1 and polyethylene glycol methacrylate are 1.3-1.5 mg / mL and 2.7-2.8 mg / mL, respectively, and bubbling under argon is performed for 45-50 min; the volume ratio of mixed solution 1, copper chloride solution, sodium ascorbate and HMTETA ligand is 20000:(2350-2450):(100-120):(35-38), the copper chloride solution is 50 mM, the sodium ascorbate is 100 mM, and the reaction is carried out at room temperature for 2-3 h.

8. The soft-polished anti-fouling tile according to claim 5, characterized in that: In S3, the concentration of the conjugate 2 solution is 2-2.2 mg / mL, and the concentration of ethanol is 40-50%. The conjugate 2 solution and ethanol are mixed in equal volumes and reacted at room temperature for 10-20 minutes.

9. The method for preparing soft-polished anti-fouling tiles according to any one of claims 1 to 8, characterized in that: The steps include: (1) preparing the green body layer: weighing corresponding weight portions of raw materials according to the formula of the green body layer, adding water, and putting them into a ball mill for ball milling to obtain a green body slurry, and then sieving to remove iron, spray granulation, aging and homogenization, pressing and forming, and drying to obtain the green body layer; (2) preparing the bottom glaze layer: weighing corresponding weight portions of raw materials according to the formula of the bottom glaze layer, adding water, putting into a ball mill for ball milling, and then removing iron to obtain a bottom glaze slurry, applying the bottom glaze on the green body to obtain the bottom glaze layer; (3) preparing a pattern layer: adding a pattern on the base glaze layer to obtain a pattern layer; (4) preparing a protective glaze layer: weighing raw materials in corresponding weight parts according to the formula of the protective glaze, adding water, putting them into a ball mill for ball milling, and then removing iron to obtain a protective glaze slurry, and applying the protective glaze on the pattern layer to obtain a protective glaze layer; (5) Firing: The ceramic tile body is obtained by placing the ceramic tile with the base glaze layer, pattern layer and protective glaze layer into a kiln for sintering; (6) Polishing: using a resin abrasive disc of a first mesh number to perform coarse grinding and polishing on the ceramic tile body to obtain a coarse polished product, then using a resin abrasive disc of a second mesh number to perform medium grinding and polishing to obtain a medium polished product, and finally using a fiber brush to perform soft grinding and polishing on the tile surface to obtain a soft polished product; (7) Cleaning: Wash the surface of the soft polished product with water and dry it to obtain a clean and dry soft polished product; (8) Spraying the antimicrobial protein-coupled antifouling coating: spraying the antimicrobial protein-coupled antifouling coating evenly on the surface of a clean and dry soft-polished product, and after film formation, obtaining a soft-polished antifouling tile pre-finished product; (9) Soak the soft-polished anti-fouling tile pre-finished product in a glutaraldehyde solution, and after the reaction is completed, wash with water and dry it to obtain the soft-polished anti-fouling tile.

10. The method for preparing soft-polished anti-fouling tiles according to claim 9, characterized in that: In step (1), step (2) and step (4), the water addition ratio is 25-35%; in step (3), the pattern is added by inkjet printing, screen printing or rubber roller printing; in step (4), a protective glaze is applied on the surface of the pattern layer by glazing, spraying or dipping, and the weight is controlled at 200-400 grams per square meter; in step (5), the firing temperature is 1100-1280°C, and the firing time is controlled at 35-60 minutes; in step (6), the mesh number of the first mesh resin grinding disc is 1 00~400, the rotation speed of the first mesh resin abrasive disc is 800~2000rpm, and the rough grinding and polishing pressure is 0.2~0.5MPa; the mesh number of the second mesh resin abrasive disc is 600~1000, the rotation speed of the second mesh resin abrasive disc is 1500~3000rpm, and the medium grinding and polishing pressure is 0.1~0.6MPa; in step (8), the antifouling coating is sprayed for 20~30min to form a film; in step (9), the concentration of glutaraldehyde solution is 1%, and the reaction time is 30~50min.

Citation Information

Patent Citations

  • Preparation method of solid phase synthesis medium based on integrated polymer material

    CN104497214A

  • Antibacterial ceramic tile and preparation method thereof

    CN113912422A

  • Anti-doodling and antifouling soft light / matte ceramic tile and preparation method thereof

    CN116640006A

Cited By

  • Soft light brick with super anti-fouling coating and preparation method of soft light brick

    CN120208640A